2018
DOI: 10.2147/cia.s183425
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between dietary nutrients intake and lipid levels with functional MRI dorsolateral prefrontal cortex activation

Abstract: BackgroundDorsolateral prefrontal cortex (DLPFC) is a key node in the cognitive control network that supports working memory. DLPFC dysfunction is related to cognitive impairment. It has been suggested that dietary components and high-density lipoprotein cholesterol (HDL-C) play a vital role in brain health and cognitive function.PurposeThis study aimed to investigate the relationships between dietary nutrient intake and lipid levels with functional MRI (fMRI) brain activation in DLPFC among older adults with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…While the attention, working memory, and executive functioning are controlled by the prefrontal cortex that is located at the frontal part of the brain, the working memory, on the other hand, was reported to have been supported by the left superior frontal, right middle frontal gyrus, and the inferior frontal gyrus . The involvement of the middle frontal gyrus in the working memory tasks such as word‐reading and numerical operations has also been proven from previous studies . Since our findings had shown the significance of right DLPFC activation from performing the N‐back tasks, we can therefore surmise that the subjects with higher ulam consumption as demonstrating a greater right‐hemispheric dominance during the visual‐spatial processing stage as compared with lower ulam consumption …”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…While the attention, working memory, and executive functioning are controlled by the prefrontal cortex that is located at the frontal part of the brain, the working memory, on the other hand, was reported to have been supported by the left superior frontal, right middle frontal gyrus, and the inferior frontal gyrus . The involvement of the middle frontal gyrus in the working memory tasks such as word‐reading and numerical operations has also been proven from previous studies . Since our findings had shown the significance of right DLPFC activation from performing the N‐back tasks, we can therefore surmise that the subjects with higher ulam consumption as demonstrating a greater right‐hemispheric dominance during the visual‐spatial processing stage as compared with lower ulam consumption …”
Section: Discussionsupporting
confidence: 78%
“…33 The involvement of the middle frontal gyrus in the working memory tasks such as word-reading and numerical operations has also been proven from previous studies. 6,33 Since our findings had shown the significance of right DLPFC activation from performing the N-back tasks, we can therefore surmise that the subjects with higher ulam consumption as demonstrating a greater righthemispheric dominance during the visual-spatial processing stage as compared with lower ulam consumption. 34 As the involvement of the middle frontal gyrus while performing the SCWT had been proven from a previous study, 23 our findings too had revealed that the subjects with higher ulam consumption as demonstrating better left DLPFC activation for both of the SCWT tasks, with the left hemisphere displaying more of the brain activity during the assigned word recognition task.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations